IODIUM MINERAL SEBAGAI ZAT GIZI - Riwayati, Riwayati (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACTIodium is one of micro substances required by body, eventhough it is in such as small relative amount.  However, once it is neglegted, it may cause the bad impact to human life.  The sufferers of Iodium Deficiency Disorder is as the burden for surrounding people.  Iodium deficiency Disorder causes mental retardism and in fact it can be prevented.  This disorder is also called as Iodium Deficiency.  The disease has not been commonly known and it is still neglected.  Nowaday, it is predicted 1,6 billions of people in all the world face the risk of iodium deficiency and 300 millions people suffer mental retardism as the effect of iodium deficiency.  Approxiamately 30,000 newborn babies died every year and more than 120,000 cretine babies such as mental retardism, short height, deaf mute, or palsied.   Some of them have IQ for ten percent under their potential.  Among those with normal newborn with low consumption of nutrient diet are those with low IQ, weak, and apathic in facing life.  Iodium deficiency will produce poor people, and face the difficulty in studying.  The risk occurs as the effect of iodium deficiency in its diet, and it has the influence on brain growth.  Iodium is as important element for forming tyroid hormone.  It is required for normal growth, mental and physical development of both human and animal.  The most dominant effect of iodium deficiency is goiter, that is the enlargement of tiroid gland in neck area. Kata Kunci : Iodium, zat gizi.